Comparative physiology of Australian echidnas (Tachyglossus aculeatus) - Barker, Justine Megan (Curtin University, 2016)
The short-beaked echidna has a combination of ancestral and derived physiological traits. Its physiology is less primitive than previously thought, with many aspects being typically mammalian, including a previously unrecognised capacity for evaporative heat loss. Echidnas have considerable metabolic, thermal and hygric plasticity to accommodate daily, seasonal and geographical environmental demands and there are significant differences in the physiology of the two most distinct sub-species.